A modified polyvinylidene fluoride coating material with graded roughness on the surface and a preparation method thereof

A modified PVDF coating with graded roughness and adjustable wettability is achieved by incorporating ionic liquids with unsaturated bonds and water vapor curing, addressing adhesion issues and enhancing stability and adhesion to diverse substrates.

CN116462878BActive Publication Date: 2025-01-03HANGZHOU NORMAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211541906.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-02
Publication Date
2025-01-03
Estimated Expiration
2042-12-02

AI Technical Summary

Technical Problem

Existing polyvinylidene fluoride (PVDF) coatings suffer from poor interfacial adhesion to substrates due to low surface energy, leading to instability and environmental pollution issues with current modification methods.

Method used

A method involving the use of ionic liquids with unsaturated bonds, such as imidazole ionic liquids, to modify PVDF, combined with a water vapor atmosphere curing to create a graded roughness on the coating surface, enhancing bonding strength and wettability.

Benefits of technology

The modified PVDF coating exhibits strong bonding strength, adjustable wettability, and improved stability under harsh conditions, with enhanced adhesion to various substrates including metal, ceramic, glass, and wood, while maintaining environmental sustainability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116462878B_ABST
    Figure CN116462878B_ABST
Patent Text Reader

Abstract

The present invention discloses a modified polyvinylidene fluoride coating material with graded roughness on the surface and a preparation method thereof. The surface of the coating material is constructed with a micro-nano two-level roughness structure and has adjustable wettability. The method of the present invention is cured in a water vapor atmosphere to construct graded roughness on the coating surface, giving the surface adjustable wettability, so that the coating has a strong bonding strength. The prepared coating material has good thermal, mechanical and chemical stability, high surface energy and bonding strength, and is expected to provide certain ideas for the in-depth development and application of fluorocarbon coatings.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coating preparation, and relates to a modified polyvinylidene fluoride coating material with graded roughness on the surface and a preparation method thereof. Background Art

[0002] Fluorocarbon coating is a general term for coatings with fluoroolefin polymers or copolymers of fluoroolefins and other monomers as film-forming materials. Fluorocarbon coatings are widely used in the fields of construction, chemical industry, electrical appliances, etc. Fluorocarbon coatings mainly include polyvinylidene fluoride (PVDF) fluorocarbon coatings and copolymers of fluoroolefins and alkyl vinyl ethers or esters (FEVE) fluorocarbon coatings. PVDF resin is a chain crystalline polymer with -CH2-CF2- as the structural unit. Polyvinylidene fluoride resin is similar to other fluorocarbon resins. The F atom has strong electronegativity, the C-F bond is strong, it is a strong polar covalent bond, and it has high chemical inertness. The present invention mainly uses commercial PVDF as the coating material, mainly because the fluorocarbon coating with PVDF as the main component shows super weather resistance and chemical resistance, and also has excellent properties such as low surface tension, low friction, hydrophobicity and self-cleaning.

[0003] CN201510246195.2 "A nanostructured polyvinylidene fluoride composite material and its preparation method" proposes that ionic liquids connected by chemical bonds are uniformly distributed in the PVDF matrix, the purpose of which is to improve the conductivity of PVDF. However, its potential in the field of coating preparation technology has not been explored. Due to the low surface energy of PVDF resin coating, its interfacial adhesion to the substrate is poor, and the construction requirements are relatively stringent. Therefore, in order to solve the problem of poor adhesion of PVDF coating to the substrate, researchers have been modifying PVDF materials to obtain PVDF materials with more stable performance. For example, in the coating system, it is usually blended with acrylic polymers to improve adhesion. However, the existing modification methods face many problems: 1. The modified material has problems of uneven performance and instability; 2. The additives cause pollution to the environment and other problems; Therefore, the present invention mainly relates to a modification method for a long-lasting and stable polyvinylidene fluoride coating.

[0004] The present invention is cured in a water vapor atmosphere to construct graded roughness on the coating surface, giving the surface adjustable wettability, so that the coating has a stronger bonding strength. Summary of the invention

[0005] The first object of the present invention is to provide a method for preparing a modified polyvinylidene fluoride coating material having a graded rough surface in view of the deficiencies in the prior art.

[0006] The specific steps of this method are as follows:

[0007] Step (1), placing polyvinylidene fluoride PVDF and ionic liquid IL in a vacuum drying oven respectively, and drying at 60-100° C. until the weight no longer decreases;

[0008] The mass ratio of the ionic liquid IL to PVDF is 2-40:100;

[0009] Preferably, the mass ratio of the ionic liquid IL to PVDF is 20:100.

[0010] The ionic liquid IL is an ionic liquid containing an unsaturated bond;

[0011] Preferably, the unsaturated bond-containing ionic liquid is an imidazole ionic liquid. The main reason is that the imidazole ionic liquid has good hydrophilicity and high surface energy, and can play a good modification role on PVDF; wherein the cationic structural formula is as follows:

[0012]

[0013] Where R1 is C1~C 24 Alkyl or containing C2~C 24 Alkenyl; R2 is C2~C 24 alkenyl;

[0014] The anion of the ionic liquid is PF6 - 、BF4 - Br - , Cl - ,I - 、NO3 - CF3CO2 - 、CH3COO - 、(CF3SO3)2N - ;

[0015] Step (2), adding the dried polyvinylidene fluoride and the ionic liquid to a melt mixing device, and melt mixing at 180 to 210° C. for 5 to 10 minutes;

[0016] Preferably, the melt mixing temperature in step (2) is 190° C. and the mixing time is 5 min.

[0017] Preferably, the melt mixing equipment is a mixer, a single screw extruder, a twin screw extruder or an injection machine or other commonly used industrial devices;

[0018] Step (3), discharging the melt-kneaded mixture from a melt-kneading device, cooling it to room temperature, and preparing a film with a thickness of 1 to 500 μm by melt-sheeting;

[0019] Step (4), placing the film obtained in step (3) in a polyethylene bag, irradiating it under vacuum at room temperature, and then performing methanol Soxhlet extraction for 72 to 144 hours to obtain an ionic liquid grafted polyvinylidene fluoride film (PVDF-g-IL);

[0020] The radiation irradiation is electron beam irradiation, and the absorbed dose is 25 to 75 kGy, preferably 50 kGy;

[0021] Step (5), at 60 to 80° C., the ionic liquid grafted polyvinylidene fluoride film obtained in step (4), the porogen and the solvent are mixed in a solution at a mass ratio of 0.92 to 0.98:0.02 to 0.08:5 for a period of time;

[0022] Preferably, the solvent is N,N-dimethylformamide (DMF);

[0023] Preferably, the porogen is polyvinyl pyrrolidone (PVP), polyethylene glycol (PEG) or polyethylene oxide (PEO);

[0024] Step (6), applying the blended solution obtained in step (5) evenly on the substrate, curing for 1-3 hours in a water vapor atmosphere at a temperature of 15-25° C. and a relative humidity of 60-80%, and drying to form;

[0025] Preferably, the curing time in step (6) is 2 hours;

[0026] The substrate includes various common materials such as metal, ceramic, glass, wood, fabric, etc.;

[0027] The preparation method mentioned above only requires the use of common solution blending equipment, and the industrial preparation is simple, and the equipment required for the radiation is a common radiation source.

[0028] Step (7), placing the modified polyvinylidene fluoride material in a sodium perfluorooctanoate (NaPFO) solution for anion exchange, and adjusting the wettability by adjusting the anion exchange time to change the hydrophilic state to the hydrophobic state.

[0029] Preferably, the concentration of the sodium perfluorooctanoate (NaPFO) solution is 0.05 to 100 mM.

[0030] Preferably, the anion exchange time is 30 to 300 s.

[0031] As an advantage, the method may further include the following steps:

[0032] Step (8), placing the modified polyvinylidene fluoride material obtained in step (7) in a sodium chloride (NaCl) solution for anion exchange, and adjusting the anion exchange time to perform reverse wettability regulation, changing the hydrophobic state to the hydrophilic state.

[0033] Preferably, the concentration of the sodium chloride (NaCl) solution is 0.1-1.0M.

[0034] Preferably, the anion exchange time is 0 to 24 hours. The regulation of wettability in step (8) and step (7) is reversible.

[0035] The second object of the present invention is to provide a modified polyvinylidene fluoride coating material with graded roughness on the surface, which is prepared by the above method and has a micro-nano two-level roughness structure on the surface, including 3-5μm microspheres and cavities, 50-200nm papillae and wrinkles; the surface is given adjustable wettability, so that the coating has a strong bonding strength.

[0036] The wettability of the material surface is determined by the chemical composition and surface morphology. In the present invention, the chemical composition of the material itself can be reversibly regulated by ion exchange. There are differences in hydrophilicity and hydrophobicity between different ions. This difference is magnified by the unique micro-nano rough structure of the surface morphology of the coating, and the water contact angle can be regulated in the range of 0° to 150°. When the coating is in a hydrophilic state, due to its good wettability to the adhesive, the bonding strength is significantly enhanced.

[0037] Beneficial effects of the present invention:

[0038] The grafted ionic liquid of the present invention has good hydrophilicity and high surface energy, so that the material can maintain a good modification effect for a long time and stably. At the same time, by curing in a water vapor atmosphere, a micro-nano graded rough structure is given to the surface of the coating, so that the coating has adjustable surface wettability and the interfacial bonding strength of the adhesive is improved.

[0039] The polyvinylidene fluoride coating of the present invention has good thermal, mechanical and chemical stability, and can adhere normally under various harsh working conditions without failure or shedding. The test conditions under which the coating of the present invention can work stably are as follows: (1) 0-150°C ambient temperature; (2) 500 times of manual bending and 50 times of tape peeling; (3) 24h immersion in various chemical reagents;

[0040] Compared with general polyvinylidene fluoride coatings, the polyvinylidene fluoride coating of the present invention has universal substrate applicability, and applicable substrates include but are not limited to various common materials such as metal, ceramic, glass, wood, and fabric; at the same time, the preparation of the polyvinylidene fluoride coating of the present invention only requires the use of commonly used melt mixing equipment and solution blending equipment, and the equipment required for its radiation is a commonly used radiation source, so the industrial preparation is simple and the processability is strong. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1is a scanning electron microscope photograph of the polyvinylidene fluoride coating, a, b and c are respectively Example 1 (3wt% IL), Example 2 (10wt% IL) and Example 3 (20wt% IL); the scale of a1, b1, c1 is 20μm, the scale of a2, b2, c2 is 10μm, and the scale of a3, b3, c3 is 5μm;

[0042] Figure 2 This is a diagram of the tape stripping process of the polyvinylidene fluoride coating, and the substrate is a PVDF membrane;

[0043] Figure 3 The tape peeling test photos of the coatings of Example 3 (a, b, c) and Comparative Examples (d, e, f), the substrates are ceramic (a, d), wood (b, e) and glass (c, f) in order;

[0044] Figure 4 This is a photo of the manual bending of the coating prepared in Example 3;

[0045] Figure 5 The thermal stability test photos of the coating prepared in Example 3 are 110°C (a), 130°C (b), 150°C (c) and 170°C (d) from left to right;

[0046] Figure 6 The SEM-Mapping photos of the chemical stability test of Example 3, from left to right are before treatment (a), strong acid treatment (b) and strong alkali treatment (c);

[0047] Figure 7 The contact angle photos of EVA melt of Example 3 and Comparative Example, (a) and (b) are Example 3 and Comparative Example respectively;

[0048] Figure 8 Schematic diagram of T-type peeling of Example 3 and Comparative Example;

[0049] Fig. 9 The T-peel strength curves of Example 3 and the comparative example;

[0050] Fig.10 Schematic diagram of adjustable wettability in Example 3; wherein (a) is anion exchange in sodium perfluorooctanoate (NaPFO) solution, changing from a hydrophilic state to a hydrophobic state; (b) is anion exchange in sodium chloride (NaCl) solution, changing from a hydrophobic state to a hydrophilic state. DETAILED DESCRIPTION

[0051] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments, but the present invention is not limited to the scope of the specific embodiments.

[0052] The present invention uses a chemical modification method of electron beam radiation grafting to uniformly distribute chemically bonded ionic liquids in a polymer material matrix. The grafted ionic liquids have good hydrophilicity and high surface energy, so that the material can maintain a good modification effect for a long time and stably. At the same time, by curing in a water vapor atmosphere, the coating surface is given a micro-nano graded rough structure, and the surface is given adjustable wettability and good bonding properties.

[0053] The polymer is polyvinylidene fluoride, which has good thermal, mechanical and chemical stability.

[0054] The above IL is preferably an ionic liquid containing an unsaturated bond. More preferably, the ionic liquid is an imidazole ionic liquid, and its structure is as follows:

[0055]

[0056] Wherein R1 is a C1-C24 alkyl or a C2-C24 alkenyl; R2 is a C2-C24 alkenyl; the anion in the ionic liquid is PF6 - 、BF4 - Br - , Cl - ,I - 、NO3 - CF3CO2 - 、CH3COO - or (CF3SO3)2N - ;

[0057] The mass fraction of the ionic liquid in the PVDF matrix is ​​2% to 40%.

[0058] Wherein, the irradiation is electron beam irradiation.

[0059] Wherein, the absorbed dose of the irradiation is 50 kGy.

[0060] The experimental conditions during the irradiation are room temperature, air and nitrogen.

[0061] In this embodiment and its comparative example, polymer PVDF is used as the matrix. The PVDF is produced by Japan Kureha Chemical Industry Co., Ltd. and its model is KF850.

[0062] The unsaturated bond-containing imidazole ionic liquid used in this embodiment is: 1-vinyl-3-butyl imidazole chloride.

[0063] The specific process of the present invention is as follows:

[0064] Example 1.

[0065] Step (1) drying the polyvinylidene fluoride and the ionic liquid in a vacuum drying oven at 80° C. overnight;

[0066] Take 50g of polyvinylidene fluoride and 1.5g of ionic liquid and add them into an internal mixer in sequence. The temperature of the internal mixer is 190°C, the rotor speed is 20rpm / min, and the internal mixing is performed for 2min. Then the rotor speed is increased to 50rpm / min, and the material is discharged after internal mixing for 5min and cooled to room temperature.

[0067] The melt-kneaded mixture was hot-pressed into a film with a thickness of 300 μm in a hot press at 190° C., a pressure of 10 MPa, and maintained at the pressure for 3 minutes.

[0068] Step (2) placing the film from step (1) in a polyethylene plastic bag for radiation irradiation, wherein the electron beam irradiation is performed at room temperature at a irradiation dose of 50 kGy;

[0069] Step (3) extracting the film of step (2) by Soxhlet extraction method, wherein the extracting solution is methanol, a good solvent for ionic liquids, and the heating temperature is controlled so that the extracting solution refluxes once every 6 to 8 minutes. The extraction time is 72 to 144 hours. After the extraction is completed, the film is taken out and dried overnight in a vacuum drying oven at 80°C to obtain a PVDF film grafted with ionic liquids.

[0070] Step (4). The film of step (3) and the porogen polyvinylpyrrolidone PVP-K30 are mixed in a certain ratio, wherein the mass ratio of the PVDF-g-IL, PVP-K30 and the solvent is 0.95:0.05:5. The temperature during the solution mixing process is set at 60-80°C, and the solvent is N,N-dimethylformamide (DMF);

[0071] Step (5) The solution obtained in step (4) is evenly applied on the PVDF substrate, cured for 2h at a temperature of 15-25°C and a relative humidity of 60-80% in a water vapor atmosphere, and dried to form;

[0072] Example 2.

[0073] Step (1) drying the polyvinylidene fluoride and the ionic liquid in a vacuum drying oven at 80° C. overnight;

[0074] Take 50g of polyvinylidene fluoride and 5g of ionic liquid and add them into an internal mixer in sequence. The temperature of the internal mixer is 190°C, the rotor speed is 20rpm / min, and the internal mixing is performed for 2min. Then the rotor speed is increased to 50rpm / min, and the material is discharged after internal mixing for 5min and cooled to room temperature.

[0075] The melt-kneaded mixture was hot-pressed into a film with a thickness of 300 μm in a hot press at 190° C., a pressure of 10 MPa, and maintained at the pressure for 3 minutes.

[0076] Step (2) placing the film from step (1) in a polyethylene plastic bag for radiation irradiation, wherein the electron beam irradiation is performed at room temperature at a irradiation dose of 50 kGy;

[0077] Step (3) extracting the film of step (2) by Soxhlet extraction method, wherein the extracting solution is methanol, a good solvent for ionic liquids, and the heating temperature is controlled so that the extracting solution refluxes once every 6 to 8 minutes. The extraction time is 72 to 144 hours. After the extraction is completed, the film is taken out and dried overnight in a vacuum drying oven at 80°C to obtain a PVDF film grafted with ionic liquids.

[0078] Step (4). The film of step (3) and the porogen polyvinylpyrrolidone PVP-K30 are mixed in a certain ratio, wherein the mass ratio of the PVDF-g-IL, PVP-K30 and the solvent is 0.95:0.05:5. The temperature during the solution mixing process is set at 60-80°C, and the solvent is N,N-dimethylformamide (DMF);

[0079] Step (5) The solution obtained in step (4) is evenly applied on the PVDF substrate, cured for 2h at a temperature of 15-25°C and a relative humidity of 60-80% in a water vapor atmosphere, and dried to form;

[0080] Example 3.

[0081] Step (1) drying the polyvinylidene fluoride and the ionic liquid in a vacuum drying oven at 80° C. overnight;

[0082] Take 50g of polyvinylidene fluoride and 10g of ionic liquid and add them into an internal mixer in sequence. The temperature of the internal mixer is 190°C, the rotor speed is 20rpm / min, and the internal mixing is performed for 2min. Then the rotor speed is increased to 50rpm / min, and the material is discharged after internal mixing for 5min and cooled to room temperature.

[0083] The melt-kneaded mixture was hot-pressed into a film with a thickness of 300 μm in a hot press at 190° C., a pressure of 10 MPa, and maintained at the pressure for 3 minutes.

[0084] Step (2) placing the film from step (1) in a polyethylene plastic bag for radiation irradiation, wherein the electron beam irradiation is performed at room temperature at a irradiation dose of 50 kGy;

[0085] Step (3) extracting the film of step (2) by Soxhlet extraction method, wherein the extracting solution is methanol, a good solvent for ionic liquids, and the heating temperature is controlled so that the extracting solution refluxes once every 6 to 8 minutes. The extraction time is 72 to 144 hours. After the extraction is completed, the film is taken out and dried overnight in a vacuum drying oven at 80°C to obtain a PVDF film grafted with ionic liquids.

[0086] Step (4). The film of step (3) and the porogen polyvinylpyrrolidone PVP-K30 are mixed in a certain ratio, wherein the mass ratio of the PVDF-g-IL, PVP-K30 and the solvent is 0.95:0.05:5. The temperature during the solution mixing process is set at 60-80°C, and the solvent is N,N-dimethylformamide (DMF);

[0087] Step (5) The solution obtained in step (4) is evenly applied on the PVDF substrate, cured for 2h at a temperature of 15-25°C and a relative humidity of 60-80% in a water vapor atmosphere, and dried to form;

[0088] Comparative Example 1.

[0089] Step (1) drying the polyvinylidene fluoride in a vacuum drying oven at 80° C. overnight;

[0090] Step (2). The polyvinylidene fluoride and porogen polyvinylpyrrolidone PVP-K30 of step (1) are mixed in a certain ratio, wherein the mass ratio of PVDF, PVP-K30 and solvent is 0.95:0.05:5. The temperature during the solution mixing process is set at 60-80°C, and the solvent is N,N-dimethylformamide (DMF);

[0091] Step (3). The solution obtained in step (2) is evenly coated on the PVDF substrate, cured for 2 hours in a water vapor atmosphere at a temperature of 15-25°C and a relative humidity of 60-80%, and dried to form.

[0092] The embodiment was subjected to scanning electron microscope detection, the experimental conditions were: gold spraying, and the results obtained were Figure 1 shown.

[0093] The samples obtained in the embodiment and the comparative example were subjected to mechanical stability test. The experimental conditions were: 50 times of tape peeling and 500 times of artificial bending. The results are shown in the figure. Figure 2-4 shown.

[0094] The samples obtained in the embodiment were tested for thermal stability, and the results were as follows: Figure 5 shown.

[0095] The samples obtained in the embodiment were subjected to SEM-Mapping test to test the chemical stability. The results are as follows Figure 6 shown.

[0096] The sample obtained in the example was subjected to melt contact angle test. The melt to be tested was EVA hot melt adhesive with a melt temperature of 130° C. The results are as follows: Figure 7 shown.

[0097] The samples obtained in the embodiment and the comparative example were subjected to T-type peeling test. The experimental conditions were as follows: the samples to be bonded were PVDF and EVA hot melt adhesives with coatings attached, the sample length was 200 mm, the width was 25 mm, the adhesive coating length was 150 mm, and the separation speed was 100 mm / min. The comparative example was PVDF and EVA hot melt adhesives without coatings attached. The other conditions were the same. The results are shown in FIG. Figure 8-9 shown.

[0098] The sample obtained in the example was subjected to adjustable wettability test. The experimental conditions were as follows: the sample was placed in a certain concentration of sodium perfluorooctanoate (NaPFO) solution for anion exchange, and the counter ions contained in the coating were exchanged from hydrophilic Cl ions to hydrophobic PFO ions; then placed in a certain concentration of sodium chloride (NaCl) solution for anion exchange, and the hydrophobic PFO ions were gradually exchanged back to hydrophilic Cl ions. The changes in the water contact angle of the coating were monitored during these two processes. The results are shown in FIG. Fig.10 shown.

[0099] like Figure 1 As shown in FIG. 1 , after being cured in a water vapor atmosphere, the polyvinylidene fluoride coating has a micro-nano two-level rough structure, including 3-5 μm microspheres and cavities, and 50-200 nm papillae and wrinkles; Figure 2-4 As shown, after 50 tape peeling tests, the polyvinylidene fluoride coating remained uniform and the appearance did not change significantly, while the comparative example mostly adhered to the tape after tape peeling, showing poor peeling strength.

[0100] like Figure 5 As shown, the polyvinylidene fluoride coating has good thermal stability and can be stably attached without falling off in an external environment of 150°C.

[0101] like Figure 6 As shown, the polyvinylidene fluoride coating has good chemical stability and can be stably attached in a strong acid and alkali environment without exposing the substrate. No signal of the substrate aluminum element is seen in the mapping diagram. The substrate is aluminum foil.

[0102] like Figure 7 As shown, the polyvinylidene fluoride coating has good wettability to the EVA melt (the left figure is an embodiment, and the right figure is a comparative example), which is beneficial to improving the bonding peel strength between the adhesive and the material to be bonded.

[0103] like Figure 8-9 As shown, the polyvinylidene fluoride coating can significantly improve the peel strength between PVDF and hot melt adhesive from 200 N / m to 950 N / m compared with the control example.

[0104] like Fig.10As shown, the polyvinylidene fluoride coating has adjustable surface wettability, and the water contact angle can be adjusted in the range of 0° to 150°.

[0105] The above embodiments are not limitations of the present invention, and the present invention is not limited to the above embodiments. As long as the requirements of the present invention are met, they belong to the protection scope of the present invention.

Claims

1. A method for preparing a modified polyvinylidene fluoride coating material having a graded rough surface, characterized in that: The preparation method comprises the following steps: Step (1), placing polyvinylidene fluoride PVDF and ionic liquid IL in a vacuum drying oven respectively, and drying at 60-100° C. until the weight no longer decreases; The mass ratio of the ionic liquid IL to PVDF is 2-40:100; The ionic liquid IL is an imidazole ionic liquid, and its cationic structure is as follows: Where R1 is C1~C 24 Alkyl or containing C2~C 24 Alkenyl; R2 is C2~C 24 alkenyl; The anion of the ionic liquid IL is PF6 - 、BF4 - Br - , Cl - ,I - 、NO3 - CF3CO2 - 、CH3COO - 、(CF3SO3)2N - ; Step (2), adding the dried polyvinylidene fluoride PVDF and the ionic liquid IL to a melt mixing device, and melt mixing at 180-210° C. for 5-10 minutes; Step (3), discharging the melt-kneaded mixture from a melt-kneading device, cooling it to room temperature, and preparing a film with a thickness of 1 to 500 μm by melt-sheeting; Step (4), placing the film obtained in step (3) in a polyethylene bag, irradiating it under vacuum at room temperature, and then performing methanol Soxhlet extraction for 72 to 144 hours to obtain an ionic liquid grafted polyvinylidene fluoride film PVDF-g-IL; The radiation irradiation is electron beam irradiation, and the absorbed dose is 25 to 75 kGy; Step (5), at 60-80° C., the ionic liquid grafted polyvinylidene fluoride film obtained in step (4), the porogen and the solvent are mixed in a mass ratio of (0.92-0.98): (0.02-0.08): 5 for a period of time; Step (6), applying the blended solution obtained in step (5) evenly on the substrate, curing for 1-3 hours in a water vapor atmosphere at a temperature of 15-25° C. and a relative humidity of 60-80%, and drying to form; Step (7), placing the modified polyvinylidene fluoride material in a sodium perfluorooctanoate NaPFO solution for anion exchange, and adjusting the wettability by adjusting the anion exchange time to change the hydrophilic state to the hydrophobic state.

2. The method for preparing a modified polyvinylidene fluoride coating material having a graded rough surface according to claim 1, characterized in that: In step (2), the melt mixing temperature is 190° C. and the mixing time is 5 min.

3. The method for preparing a modified polyvinylidene fluoride coating material having a graded rough surface according to claim 1, characterized in that: The absorbed dose of radiation exposure in step (4) is 50 kGy.

4. The method for preparing a modified polyvinylidene fluoride coating material having a graded rough surface according to claim 1, characterized in that: In step (5), the solvent is N,N-dimethylformamide DMF; and the porogen is one of polyvinyl pyrrolidone PVP, polyethylene glycol PEG or polyethylene oxide PEO.

5. The method for preparing a modified polyvinylidene fluoride coating material having a graded rough surface according to claim 1, characterized in that: The substrate in step (6) is metal, ceramic, glass, wood or fabric.

6. The method for preparing a modified polyvinylidene fluoride coating material having a graded rough surface according to claim 1, characterized in that: In step (7), the concentration of the sodium perfluorooctanoate NaPFO solution is 0.05 to 100 mM; and the anion exchange time is 30 to 300 s.

7. The method for preparing a modified polyvinylidene fluoride coating material having a graded rough surface according to claim 1, characterized in that: After step (7), the method further includes reverse wettability regulation; The reverse wettability regulation is specifically to place the modified polyvinylidene fluoride material obtained in step (7) in a sodium chloride NaCl solution for anion exchange, and to regulate the wettability by regulating the anion exchange time, so as to change the hydrophobic state into the hydrophilic state.

8. The method for preparing a modified polyvinylidene fluoride coating material having a graded rough surface according to claim 7, characterized in that: The concentration of the sodium chloride NaCl solution is 0.1 to 1.0 M; the anion exchange time is 0 to 24 h.

9. A modified polyvinylidene fluoride coating material having a graded rough surface, prepared by the method of any one of claims 1 to 8, characterized in that: The surface of the coating material is constructed with a micro-nano two-level rough structure, including microspheres and cavities of 3 to 5 μm, and papillae and wrinkles of 50 to 200 nm; the coating material has adjustable surface wettability.